Migration Networks and the Transnationalization of social capital: cornish migration to the pacific littoral - Schwartz, Sharron (Revista de Historia Social y de las Mentalidades, 2017)
This article aims to evaluate the contribution of regional migrations to the expansion of british industry throughout the XIX century. It questions the homogeneity of the movement of britons to the west coast stressing the migration of cornishmen through available archives. It also identifies trends of migrations resorting to a case study in the chilean port of tocopilla. It also analyses how the “social capital” of migrants contributed to the formation of communities and social networks which contributed to the heterogeneity of the migration into the region under study.
Keywords: Migrations; Cornwall; West Coast; Social Capital